From Sundance to suspect: a rhetorical analysis of the Nate Parker controversy - Lamb, David Connor (Kansas State University, 2017)
Artists influence society. We also often consider the question of whether we can or should separate the art and the artist. In January 2016 The Birth of a Nation premiered at the Sundance Film Festival to near unanimous praise. Shortly after the release, past allegations of sexual assault against the filmmaker, co-writer, and star Nate Parker’s past came to light. This revelation about his past continues a long and unfortunate history of artists who have completed culturally relevant works but who have been morally suspect human beings. I therefore explore how communities reconcile and support an artist accused of reprehensible acts or how they condemn the artist and reject support for them or their work. I find that commentators who engage in this controversy call forth specific communities. These communities are bound by their identities, and I suggest how they potentially are able to move forward, grow, and possibly come together across lines that include gender, race, ideology, social status, and personal identity and how they communicate and grow as individuals. Through revised discourse, these communities may be able to one day communicate across cultural lines that are currently deep chasms, separated by ideology and identity.
Keywords: Race; Gender; Identity; Ideology; Cross-cultural communication